Effect of Caffeine on Perceived Soreness and Functionality Following an Endurance Cycling Event. Issue 3 (March 2017) - Caldwell, Aaron R.; Tucker, Matthew A.; Butts, Cory L.; McDermott, Brendon P.; Vingren, Jakob L.; Kunces, Laura J.; Lee, Elaine C.; Munoz, Colleen X.; Williamson, Keith H.; Armstrong, Lawrence E.; Ganio, Matthew S.
Abstract : Abstract: Caldwell, AR, Tucker, MA, Butts, CL, McDermott, BP, Vingren, JL, Kunces, LJ, Lee, EC, Munoz, CX, Williamson, KH, Armstrong, LE, and Ganio, MS. Effect of caffeine on perceived soreness and functionality following an endurance cycling event. J Strength Cond Res 31(3): 638–643, 2017—Caffeine can reduce muscle pain during exercise; however, the efficacy of caffeine in improving muscle soreness and recovery from a demanding long-duration exercise bout has not been established. The purpose of this study was to investigate the effects of caffeine intake on ratings of perceived muscle soreness (RPMS) and perceived lower extremity functionality (LEF) following the completion of a 164-km endurance cycling event. Before and after cycling RPMS (1-to-6; 6 = severe soreness) and LEF (0-to-80; 80 = full functionality) were assessed by questionnaires. Subjects ingested 3 mg/kg body mass of caffeine or placebo pills in a randomized, double-blind fashion immediately after the ride and for the next 4 mornings (i.e., ∼800 hours) and 3 afternoons (i.e., ∼1200 hours). Before each ingestion, RPMS and LEF were assessed. Afternoon ratings of LEF were greater with caffeine ingestion the first day postride (65.0 ± 6.1 vs. 72.3 ± 6.7; for placebo and caffeine, respectively; p = 0.04), but at no other time points ( p > 0.05). The caffeine group tended to have lower overall RPMS in the afternoon versus placebo (i.e., main effect of group; 1.1 ± 0.2 vs. 0.5 ± 0.2; p = 0.09). Afternoon RPMS for the legs was significantly lower in the caffeine group (main effect of caffeine; 1.3 ± 0.2 vs. 0.5 ± 0.3; p = 0.05). In conclusion, ingesting caffeine improved RPMS for the legs, but not LEF in the days following an endurance cycling event. Athletes may benefit from ingesting caffeine in the days following an arduous exercise bout to relieve feelings of soreness and reduced functionality.